A Learner-Engaging Reading Lesson - Gnawali, Laxman (Journal of NELTA, 2018)
Teaching reading skill in the EFL classroom in Nepal and other countries with similar contexts is often a teacher-dominant phenomenon. Allowing and facilitating learners to take charge of the interactions with the text cannot only make lessons more interesting but prepare the learners to be in a position to develop independent reading skills for real life situations. This lesson illustrates the teaching of reading in which learners are actively engaged in the whole process while the teacher facilitates the process. Journal of NELTA, Vol. 22, No. 1-2, 2017 December, Page: 143-146